1977
DOI: 10.1021/jo00431a024
|View full text |Cite
|
Sign up to set email alerts
|

Reaction of 2-norbornyl- and 3,3-dimethyl-2-norbornylmagnesium bromide with acetone

Abstract: Attempts to determine the stereochemistry of electrophilic addition of acetone to two configurationally rigid Grignard reagents [2-norbornylmagnesium bromide (3) and 3,3-dimethyl-2-norbornylmagnesium bromide (9)] are described. Evidence is presented which suggests that the reaction of 9 with benzophenone proceeds via an electrontransfer pathway. In addition, results describing an improved synthesis of camphenilone and the stereospecific synthesis of exo-2-bromo-3,3-dimethylnorbornane are presented.Despite its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
4
0

Year Published

1977
1977
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 8 publications
(12 reference statements)
1
4
0
Order By: Relevance
“…Transmetalation of an equilibrium mixture of 3 to zinc and further reaction with an excess of 1b yielded a 65:35 endo : exo mixture of amine 5 in 55% yield (Scheme ). This is similar to published ratios obtained for carbonation,8a mercuration,8a and amination . After establishing that both isomers react similarly, we examined the resolved isomer.…”
supporting
confidence: 91%
See 1 more Smart Citation
“…Transmetalation of an equilibrium mixture of 3 to zinc and further reaction with an excess of 1b yielded a 65:35 endo : exo mixture of amine 5 in 55% yield (Scheme ). This is similar to published ratios obtained for carbonation,8a mercuration,8a and amination . After establishing that both isomers react similarly, we examined the resolved isomer.…”
supporting
confidence: 91%
“…We next examined the fate of a stereodefined R* 2 Zn reagent when subjected to the amination conditions. The Grignard reagents 3 -endo and 4 were chosen to conduct the study (Scheme ). Though conveniently prepared, the use of 3- endo is not completely unbiased, as the reaction of interest must proceed through diastereomeric transition states.…”
mentioning
confidence: 99%
“…To date, only one example of a non-heteroatom-stabilized α-chiral Grignard reagent has been reported, which was prepared via a sulfoxide-magnesium exchange. 2 Furthermore, deracemization of a mixture of endo- and exo- norbornylmagnesium bromide using benzophenone 3 or exploiting the different reactivities of menthylmagnesium chloride epimers 4 have been reported. Recently, we have shown that various enantiomerically enriched secondary alkyl iodides of type 1 underwent an I/Li-exchange 5 at −100 °C in pentane:ether mixtures furnishing the corresponding chiral alkyllithiums of type 2 with retention of configuration ( Scheme 1a ).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the stereochemical probes such as 4 12,13 and 5 14 have been used to probe the mechanism of Grignard additions. 15,16 Yet in the case of 4 and 5 it is a moot point, to what extent the stereochemical outcome is influenced by the presence of the additional stereogenic centres (only one case of epimerisation 13 has been so far observed). The ideal probe would be a Grignard reagent such as 6, in which the magnesium-bearing carbon atom is the sole stereogenic centre.…”
mentioning
confidence: 99%
“…This is in line with the finding for the carboxylation of 5. 14 As the addition of formaldehyde to 5 proceeded as well without epimerisation, 15 we looked at the addition of 6 to aromatic aldehydes, where the intervention of electron transfer steps is more likely. Addition of 6 to aldehydes generates two diastereomeric adducts (D1; D2), which were derivatized with Mosher's reagent and analysed by 1 H-NMR spectroscopy.…”
mentioning
confidence: 99%